The changing paths of progress - Abd Razak, Dzulkifli (2009)
THE prime minister addressed groups of student leaders and public service officers in succession over the week. The theme that ran through these meetings was change. But it is not just any type of change. Rather, it was one that is transformational in nature and had a significant impact on the wellbeing of society. A change that is relevant not just for today, but also for the needs of tomorrow with all its complexities. Linear and homogenous changes are no longer deemed as sufficient.